2016
DOI: 10.1111/jog.13015
|View full text |Cite
|
Sign up to set email alerts
|

Successful term delivery of spontaneous twin pregnancy in a woman with bicorporeal septate uterus: A case report

Abstract: Herein, we report the first case of successful term delivery of twins in a patient with bicorporeal septate uterus via natural conception. The patient had been diagnosed with complete septate, didelphys and bicornuate uterus during different phases of her three pregnancies. Based on follow-up data at six weeks and then six months post-partum of the last pregnancy, we found that the abnormalities presented in our case did not fit the criteria of any categories following American Fertility Society and European S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The most common indications for cesarean section in the literature include malpresentation, [7][8][9]12,27,28 fetal distress, 13,18,26 labor dystocia, 5,10 and concern for obstruction of the birth canal. 21,24 In the case of our patient, a second cervix was never palpated or visualized on exam during the antepartum period, despite visualization of a second cervical canal on ultrasound. Given this concern and breech presentation of both twins at term, a cesarean was scheduled for 37 weeks gestation.…”
Section: Mode Of Deliverymentioning
confidence: 56%
See 2 more Smart Citations
“…The most common indications for cesarean section in the literature include malpresentation, [7][8][9]12,27,28 fetal distress, 13,18,26 labor dystocia, 5,10 and concern for obstruction of the birth canal. 21,24 In the case of our patient, a second cervix was never palpated or visualized on exam during the antepartum period, despite visualization of a second cervical canal on ultrasound. Given this concern and breech presentation of both twins at term, a cesarean was scheduled for 37 weeks gestation.…”
Section: Mode Of Deliverymentioning
confidence: 56%
“…However, a dicavitary gestation is not itself a contraindication for vaginal birth unless the birth canal is incomplete or obstructed. The most common indications for cesarean section in the literature include malpresentation, 7–9,12,27,28 fetal distress, 13,18,26 labor dystocia, 5,10 and concern for obstruction of the birth canal 21,24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, pregnancy may be possible after surgical corrections through natural or artificial insemination ( Table 2 ). In a rare case, Li et al . (2016) reported a successful full-term twin pregnancy in each cavity of a bicorporeal septate uterus of a patient with two cervices and a longitudinal vaginal septum via natural insemination.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, pregnancy may be possible after surgical corrections through natural or artificial insemination (Table 2). In a rare case, Li et al (2016) reported a successful full-term twin pregnancy in each cavity of a bicorporeal septate uterus of a patient with two cervices and a longitudinal vaginal septum via natural insemination. Furthermore, a women with bicornuate unicollis uterus with twins successfully delivered at 35 weeks of gestation through a bilateral cesarean section (Doruk et al, 2013).…”
Section: Congenital Uterine Malformations (N=432) Pmentioning
confidence: 99%